2020
DOI: 10.1111/luts.12335
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of mirabegron in male patients with overactive bladder with or without benign prostatic hyperplasia: A Japanese post‐marketing study

Abstract: Objectives: The aim of this post hoc analysis from the Japanese mirabegron surveillance program was to investigate the safety and effectiveness of mirabegron in male patients with overactive bladder (OAB) symptoms with/without concomitant benign prostatic hyperplasia (BPH). Methods: This 12-week study included patients who were starting mirabegron treatment for the OAB symptoms of urinary urgency, daytime frequency, and urgency urinary incontinence. Patients were stratified according to BPH diagnosis, and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(70 reference statements)
0
12
0
1
Order By: Relevance
“…Size stratification of the prostate too was not considered in this study bearing in mind that bothersome LUTS are usually largely independent of prostate size. Considering the longer duration (12 weeks) of other Mirabegron published trials 26,27 one could question our shorter duration of study. For reasons described previously the present 8‐week follow‐up was performed in this protocol considering the fact that both drugs in the study had rapid onset of action and majority of their usual side effects if any would be exhibited well within this time frame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size stratification of the prostate too was not considered in this study bearing in mind that bothersome LUTS are usually largely independent of prostate size. Considering the longer duration (12 weeks) of other Mirabegron published trials 26,27 one could question our shorter duration of study. For reasons described previously the present 8‐week follow‐up was performed in this protocol considering the fact that both drugs in the study had rapid onset of action and majority of their usual side effects if any would be exhibited well within this time frame.…”
Section: Discussionmentioning
confidence: 99%
“…We did not attempt examine the effect of Mirabegron in patients of OABS without BPE in this study, however, in a post‐marketing study by Takahashi et al 26 using 12 week Mirabegron therapy for OABS patients [with/without BPH on 4540 (3176 diagnosed with BPE)] in which the occurrences of AUR and the concomitant use of α1‐blockers were specifically investigated, the authors concluded that Mirabegron was well‐tolerated and effective for majority of their patients with OABS with or without concomitant BPE 26 . In a multicentre, randomised, double‐blind, placebo‐controlled, parallel comparison phase IV mirabegron study by Shin et al 27 conducted exclusively on 464 males with OABS the authors concluded that mirabegron was well tolerated for 26 weeks, without additional adverse effects compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of BPH is clinically and academically defined in various ways, and IPSS, PV, and rectal examination are used as diagnostic criteria in various papers 12‐14 . Due to the nature of the research conducted on patients at the health promotion center, benign prostatic hyperplasia/lower urinary tract symptoms (BPH/LUTS) was defined as an IPSS of eight points or higher to classify patient groups based on IPSS.…”
Section: Methodsmentioning
confidence: 99%
“…ДГПЗ може спричи-няти ГСМ внаслідок холінергічної денервації детрузора та послідовної гіперчутливості мускаринових рецепторів до ацетилхоліну. Порушення детрузора СМ може бути також наслідком ішемії, збільшення вмісту колагену в детрузорі, змін електричних властивостей гладком'язових клітин та реорганізації спінального рефлексу сечовипускання Після усунення обструкції відбувається реіннервація СМ і відновлення стабільності детрузора [20].…”
Section: основний зміст роботиunclassified